Pelatihan Ecoprint Teknik Pounding untuk Pengembangan Kreativitas Siswa Sekolah Dasar Negeri 01 Percontohan Aceh Barat - Sampena, Iwan Doa; Ananda, Cindy; Nisrina, Nurmai; Jonsa, Alimas; Sudarman, Sudarman; Latif, Ikhwan Rahmatika; Saputra, Ilham Mirza; Nova, Mirza Adia (Universitas Teuku Umar, 2025)
Environmental degradation, particularly caused by plastic waste, remains a global issue that requires comprehensive management and the involvement of various stakeholders. One effective approach is the provision of environmental education from an early age through innovative and engaging methods. This community service activity aimed to foster environmental awareness and enhance children’s creativity through ecoprint training using the pounding technique at SDN 01 Percontohan, West Aceh. The activity consisted of socialization, hands-on training, and evaluation using pretests and posttests, involving 40 fifth-grade students. The results showed an increase in students’ knowledge of environmental conservation as well as their ability to create artwork from natural materials. The students successfully produced tote bags with unique ecoprint motifs, which contributed to the improvement of their motor skills and their sense of responsibility toward the environment. Overall, ecoprint training proved effective in enhancing students’ environmental awareness and creativity. The success of this program has encouraged the expansion of similar activities to other schools to help develop a generation that is more environmentally conscious.